Neo‐Adjuvant chemotherapy and its affects to the axilla—Can we safely downgrade axillary surgery to mirror the approach in the breast. Issue 9 (6th August 2020) - Batt, Jeremy; Chambers, Alice; Al‐Allak, Asmaa; Vestey, Sarah; Hunt, Richard; Massey, Eleanore; Fowler, Clare
Abstract: The use of neo‐adjuvant chemotherapy (NACT) to downgrade surgery in the breast from mastectomy to breast‐conserving surgery is well‐established. In certain patients, the use of adjuvant axillary radiotherapy can be safe and effective in place of axillary node clearance. What remains less clear are the alternative surgical options to the axilla following NACT. The aim of this study was to examine the effects of NACT in the axilla and whether downgrading axillary node clearance to axillary conserving surgery to mirror the approach in the breast may be a viable and safe practice. Patients undergoing neo‐adjuvant chemotherapy were identified over a seven‐year period between 2010 and 2017. Surgical plans were compared with pre‐ and post‐chemotherapy. Histological information at the time of diagnosis was compared to surgical excision specimens. 349 patients were included for analysis, and 264 had axillary status documented at diagnosis. The average patient age was 51 years, and Grade 3, ER‐positive, and Her2‐negative cancers made the biggest histological subgroups. Complete pathological response (CPR) was seen in the breast in 27% of cases. 19% of patients requiring mastectomy had their surgery downgraded. Following NACT, axillary CPR was seen in 42% of patients and residual axillary nodal burden was limited to four nodes in 73% of patients. Axillary conserving surgery may be a safe alternative surgical approach in the downstaged axilla following neo‐adjuvant chemotherapy. Advances in perioperative identification of suspicious nodes may be needed to facilitate progress.